Biomass harvesting cost analysis using field scale testing data - Brokesh, Edwin (Kansas State University, 2019)
In 2008 AGCO began a project to develop machinery to harvest biomass for a DOE project called “Integration of Advanced Logistical Systems and Focused Bioenergy Harvesting Technologies to supply Crop Residues and A Herbaceous Energy Crops in a Diversified Large Square Bale Format”. The project considered the harvest of corn stover, wheat straw, switchgrass and energy sorghum. AGCO modified some existing pieces of production hay harvesting equipment and developed a new larger square baler for single pass crop residue harvesting. Field scale tests of the developed equipment occurred in the years 2010, 2011, and 2012. Data collected during these tests included crop harvested, field location, number of hectares harvested, moisture content of harvested biomass, number of bales produced, weight of each bale, time to harvest, model(s) and sizes of machine(s) used, and fuel consumed. Data was collected for different harvesting techniques for crop residues: two-pass vs single-pass harvesting for corn stover and wheat straw. Data was collected for harvesting switchgrass and energy sorghum for comparison purposes. The cropping years were very different over the course of the project due rain fall amounts. The data was analyzed using American Society of Agricultural and Biological Engineer machinery management standards and accepted Agriculture & Applied Economics Association assumptions. Excel spreadsheets were developed to calculate the harvesting costs on a dry Mg basis for each crop that was harvested. Results from the data analysis was used to modify the Integrated Biomass Supply Analysis and Logistics model to predict harvesting costs for crop residues at different yield levels, harvest conditions, and machine settings for single-pass harvesting. A number of conclusions can be drawn from this analysis. First, “take rates” for crop residues can have a significant effect on harvest costs. Low “take rates” can make it economically unfeasible to harvest crop residues in some instances. Second, single-pass harvesting of crop residues is less labor and fuel intensive than multi-pass harvesting. Third, the large yields potential of energy sorghum, which requires more operations to harvest than switchgrass, more economically to harvest than switchgrass. Fourth, operational techniques can be used to offset some crop variability to reduce harvest cost of crop residues. Lastly, a decision tool has been developed to aid producers in the decision of whether to harvest corn stover or not based on cost return estimates.
Keywords: Corn stover harvesting; Stover harvest variability; Single-pass harvesting; Two-pass harvesting; Integrated Biomass Supply and Logistics Model; IBSAL